X+((-3)x)=-8

Simple and best practice solution for X+((-3)x)=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+((-3)x)=-8 equation:


Simplifying
X + ((-3) * x) = -8

Solving
X + (-3x) = -8

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '(3x)' to each side of the equation.
X + (-3x) + (3x) = -8 + (3x)

Combine like terms: (-3x) + (3x) = 0
X + 0 = -8 + (3x)
X = -8 + (3x)

Simplifying
X = -8 + (3x)

See similar equations:

| 7x+17=-4 | | 2x+2=2(x-7) | | -3x-(-8)=x | | -y=8x | | -6(2r+4)=-84 | | O=4x+(-6x+7) | | -4y+4=-2(3y+7) | | 6t-4=2 | | x+2x+14=83 | | 3x+20=-1 | | f(f(t^2))=x+5 | | 28+4y-10=14y-14-2y | | -5[3+5(-3+5)]+12= | | -6(12-2w)=7(-2-3w) | | 3(2x-6)+(-6)(2x-4)= | | -64=4(-6m+2) | | 3y^2-19y+6=0 | | 20u-13+16u+33= | | -64=(-6m+2) | | 5n^2-7n-34=0 | | 3(-9)-(-13)= | | x+19+2x=-11-2x-15 | | 16x^2=764 | | 9+6(-4)= | | 6(2x-4)=3(-x+7) | | 6c+9-5c-5= | | x^10-k^2=0 | | 17x-3x= | | x^10-k^3=0 | | 0.04x^2=21.16 | | x^10-k=0 | | 3(2k-5)=k |

Equations solver categories